The m6A mRNA demethylase FTO in granulosa cells retards FOS-dependent ovarian aging - Zhong-xin Jiang; Yi-ning Wang; Zi-yuan Li; Zhi-hui Dai; Yi He; Kun Chu; Jia-yi Gu; Yi-Xuan Ji; Ning-xia Sun; Fu Yang; Wen Li (Cell Death and Disease, 2021)
Abstract Multifunctional N6-methyladenosine (m6A) has been revealed to be an important epigenetic component in various physiological and pathological processes, but its role in female ovarian aging remains unclear. Thus, we demonstrated m6A demethylase FTO downregulation and the ensuing increased m6A in granulosa cells (GCs) of human aged ovaries, while FTO-knockdown GCs showed faster aging-related phenotypes mediated. Using the m6A-RNA-sequence technique (m6A-seq), increased m6A was found in the FOS-mRNA-3′UTR, which is suggested to be an erasing target of FTO that slows the degradation of FOS-mRNA to upregulate FOS expression in GCs, eventually resulting in GC-mediated ovarian aging. FTO acts as a senescence-retarding protein via m6A, and FOS knockdown significantly alleviates the aging of FTO-knockdown GCs. Altogether, the abovementioned results indicate that FTO in GCs retards FOS-dependent ovarian aging, which is a potential diagnostic and therapeutic target against ovarian aging and age-related reproductive diseases.